Establishment of linkage on all financial actors in the financial ecosystem a technology foresight in financial innovation in the Philippines in year 2022 - Cabrera, Dancelle Daine Roman (University of the Philippines Diliman, 2017)
The age of technology has been rapidly accelerating in the Philippines and has immensely create a great dissolution to the conventional ways of life per se and shape it into a totally different perspective. There are several startup groups and companies developing tech - based solutions for consumers in emerging markets and has seen growing opportunities in the country today. They view the country as a good testing ground for tech products and services having potential in a global scale. In this study, the researcher focused on one of its application in the perspective of the financial ecosystem. The motivation of the researcher's study is to realize how to unlock an economic opportunity for the poor and to apprehend the role of technology in innovating the financial system in the Philippines.